Uglevody v sporte vysshih dostizhenij: stabil'nost' i innovacii ispol'zovanija - Dmitriyev, A.; Gunina, L. (Science in Olympic Sport, 2019)
Objective. To form modern ideas about carbohydrates as macronutrients with a diverse function in the athlete's body. Methods. Analysis and generalization of scientific and methodological literature data on the subject under study, as well as analysis of the results of reference databases. Results. The review article provides a modern classification of carbohydrates according to the criteria of the Food and Agriculture Organization of the United Nations (FAO). The article considers the eff ect of diff erent types of carbohydrates on the main metabolic processes and integral indices of the state of organs and systems during physical loads, highlights the role of carbohydrates in regulating the athlete's intestinal microbiome and provides recommendations on the real daily carbohydrate consumption in various sports events. Emphasis is placed on the fact that currently, skilled athletes specializing in various sports are deficient in carbohydrates in the diet from 360% of the required daily consumption in rowing, kayaking and canoeing to 915% in handball. New types of carbohydrates (highly branched cyclic dextrin) that support the body immune function in the dynamics of the training process as well as positively aff ect the severity of stress responses mediated by training and competitive loads are described. Conclusions. Therefore, carbohydrates are not only macronutrients, providing the overwhelming amount of energy entering the body, but also have an immunotropic, probiotic and regulatory function, which induces the need for correction of carbohydrate rations in the direction of increasing their average daily intake in accordance with recommendations of reputable expert organizations.